Handbook of photonics for biomedical science - Tuchin, V. V. (Valeriĭ Viktorovich) (Boca Raton, FL : CRC Press, 2010)
Describes advanced biophotonics methods and techniques. This comprehensive handbook covers the mathematical modeling of light-tissue interactions, spectroscopy and imaging methods for biomedical diagnostics, nonlinear spectroscopies for molecular-level cell and tissue imaging, and advanced spectroscopy and imaging of various tissues
FDTD Simulation of Light Interaction with Cells for Diagnostics and Imaging in Nanobiophotonics, Stoyan Tanev, Wenbo Sun, James Pond, and Valery V. Tuchin Plasmonic Nanoparticles: Fabrication, Optical Properties, and Biomedical Applications, Nikolai G. Khlebtsov and Lev A. Dykman Transfection by Optical Injection, David J. Stevenson, Frank J. Gunn-Moore, Paul Campbell, and Kishan Dholakia Advances in Fluorescence Spectroscopy and Imaging, Herbert Schneckenburger, Petra Weber, Thomas Bruns, and Michael Wagner Applications of Optical Tomography in Biomedical Research, Ana Sarasa-Renedo, Alex Darrell, and Jorge Ripoll Fluorescence Lifetime Imaging and Metrology for Biomedicine, Clifford Talbot, James McGinty, Ewan McGhee, Dylan Owen, David Grant, Sunil Kumar, Pieter De Beule, Egidijus Auksorius, Hugh Manning, Neil Galletly, Bebhinn Treanor, Gordon Kennedy, Peter M.P. Lanigan, Ian Munro, Daniel S. Elson, Anthony Magee, Dan Davis, Mark Neil, Gordon Stamp, Christopher Dunsby, and Paul French Raman and CARS Microscopy of Cells and Tissues, Christoph Krafft and Jurgen Popp Resonance Raman Spectroscopy of Human Skin for the In Vivo Detection of Carotenoid Antioxidant Substances, Maxim E. Darvin and Juergen Lademann Polarized Light Assessment of Complex Turbid Media Such as Biological Tissues Using Mueller Matrix Decomposition, Nirmalya Ghosh, Michael Wood, and Alex Vitkin Statistical, Correlation, and Topological Approaches in Diagnostics of the Structure and Physiological State of Birefringent Biological Tissues, O.V. Angelsky, A.G. Ushenko, Yu.A. Ushenko, V.P. Pishak, and A.P. Peresunko Biophotonic Functional Imaging of Skin Microcirculation, Martin J. Leahy and Gert E. Nilsson Advances in Optoacoustic Imaging, Tatiana Khokhlova, Ivan Pelivanov, and Alexander Karabutov Optical-Resolution Photoacoustic Microscopy for In Vivo Volumetric Microvascular Imaging in Intact Tissues, Song Hu, Konstantin Maslov, and Lihong V. Wang Optical Coherence Tomography Theory and Spectral Time-Frequency Analysis, Costas Pitris, Andreas Kartakoullis, and Evgenia Bousi Label-Free Optical Micro-Angiography for Functional Imaging of Microcirculations within Tissue Beds In Vivo, Lin An, Yali Jia, and Ruikang K. Wang Fiber-Based OCT: From Optical Design to Clinical Applications, V. Gelikonov, G. Gelikonov, M. Kirillin, N. Shakhova, A. Sergeev, N. Gladkova, and E. Zagaynova Noninvasive Assessment of Molecular Permeability with OCT, Kirill V. Larin, Mohamad G. Ghosn, and Valery V. Tuchin Confocal Light Absorption and Scattering Spectroscopic Microscopy, Le Qiu and Lev T. Perelman Dual Axes Confocal Microscopy, Michael J. Mandella and Thomas D. Wang Nonlinear Imaging of Tissues, Riccardo Cicchi, Leonardo Sacconi, and Francesco Pavone Endomicroscopy Technologies for High-Resolution Nonlinear Optical Imaging and Optical Coherence Tomography, Yicong Wu and Xingde Li Advanced Optical Imaging of Early Mammalian Embryonic Development, Irina V. Larina, Mary E. Dickinson, and Kirill V. Larin Terahertz Tissue Spectroscopy and Imaging, Maxim Nazarov, Alexander Shkurinov, Valery V. Tuchin, and X.-C. Zhang Nanoparticles as Sunscreen Compound: Risks and Benefits, Alexey P. Popov, Alexander V. Priezzhev, Juergen Lademann, and Risto Myllyla Photodynamic Therapy/Diagnostics: Principles, Practice, and Advances, Brian C. Wilson Advances in Low-Intensity Laser and Phototherapy, Ying-Ying Huang, Aaron C.-H. Chen, and Michael R. Hamblin Low-Level Laser Therapy in Stroke and Central Nervous System, Ying-Ying Huang, Michael R. Hamblin, and Luis De Taboada Advances in Cancer Photothermal Therapy, Wei R. Chen, Xiaosong Li, Mark F. Naylor, Hong Liu, and Robert E. Nordquist Cancer Laser Thermotherapy Mediated by Plasmonic Nanoparticles, Georgy S. Terentyuk, Garif G. Akchurin, Irina L. Maksimova, Galina N. Maslyakova, Nikolai G. Khlebtsov, and Valery V. Tuchin "All Laser" Corneal Surgery by Combination of Femtosecond Laser Ablation and Laser Tissue Welding, Francesca Rossi, Paolo Matteini, Fulvio Ratto, Luca Menabuoni, Ivo Lenzetti, and Roberto Pini Index
Includes bibliographical references and index.
Keywords: Imaging systems in medicine -- Handbooks, manuals, etc; Phototherapy -- Handbooks, manuals, etc; Photobiology -- Handbooks, manuals, etc; Photonics -- Handbooks, manuals, etc; Nanophotonics -- Handbooks, manuals, etc; Photobiology -- methods; Microscopy -- methods; Phototherapy